2021
DOI: 10.1016/j.apsb.2021.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The biology, function, and applications of exosomes in cancer

Abstract: Exosomes are cell-derived nanovesicles with diameters from 30 to 150 nm, released upon fusion of multivesicular bodies with the cell surface. They can transport nucleic acids, proteins, and lipids for intercellular communication and activate signaling pathways in target cells. In cancers, exosomes may participate in growth and metastasis of tumors by regulating the immune response, blocking the epithelial–mesenchymal transition, and promoting angiogenesis. They are also involved in the development of resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
218
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(221 citation statements)
references
References 180 publications
(219 reference statements)
3
218
0
Order By: Relevance
“…Moreover, a growing number of studies have revealed the presence of ectoproteases in EVs derived from TME. EVs are small cell-derived membrane vesicles, produced either through the endosomal pathway, giving rise to exosomes, or after budding of plasma membrane, resulting in microvesicles [243][244][245][246]. EVs obtained from the serum of cancer patients holds promise as diagnostic and prognostic parameters [229,247,248].…”
Section: New Avenues For Ectoproteases In the Context Of Cancer Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a growing number of studies have revealed the presence of ectoproteases in EVs derived from TME. EVs are small cell-derived membrane vesicles, produced either through the endosomal pathway, giving rise to exosomes, or after budding of plasma membrane, resulting in microvesicles [243][244][245][246]. EVs obtained from the serum of cancer patients holds promise as diagnostic and prognostic parameters [229,247,248].…”
Section: New Avenues For Ectoproteases In the Context Of Cancer Therapymentioning
confidence: 99%
“…EVs influence tumour growth, metastasis, epithelial-to-mesenchymal transition, and drug resistance [229,[247][248][249]. Exosomes transfer various molecules from tumour cells to immune cells and neovascular cells, contributing to the escape from immune surveillance and increased angiogenesis, respectively [231,245,246]. DPP4, APN, ADAM17, and MMP2/9 were recently described in EVs derived from solid and haematological tumours [242,[250][251][252][253][254][255][256][257].…”
Section: New Avenues For Ectoproteases In the Context Of Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes excluded from MSC are involved in second tumor niche formation and the development of chemoresistance. Exosomes include a shortened cancer repertoire with crucial for disease progression molecules, e.g., proteins and non-coding regulatory RNAs fraction [59]. MSCs, circulating tumor cells, and exosome might be one of the aims for targeted therapy in metastatic lung cancer [60].…”
Section: Tumor Stromamentioning
confidence: 99%
“…Extracellular vesicles (EVs), such as microvesicles and exosomes, are nanosized vesicles with lipid membranes that are secreted by most cells. EVs contain many bioactive molecules, such as microRNAs (miRNAs), long noncoding RNAs (lncRNAs), circular RNAs (circRNAs), and proteins, and these EV cargoes regulate intercellular communication ( Mathieu et al, 2019 ; Liu et al, 2021 ). Donor cell-derived EVs are taken up by recipient cells, and the encapsulated bioactive components are thus delivered to recipient cells, enabling their regulation of recipient cell biological behaviors.…”
Section: Introductionmentioning
confidence: 99%